How does it sound? [voice clarity analysis]. - Denisowski, P.
In this paper, the author describes how, in order to check voice quality, designers of compressed and packetized data networks are enlisting computer-based techniques
Keywords: Compressed data networks; Computer-based techniques; Packetized data networks; Voice clarity analysis; Voice quality checking